2014
DOI: 10.1016/j.dnarep.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule techniques in DNA repair: A primer

Abstract: A powerful new approach has become much more widespread and offers insights into aspects of DNA repair unattainable with billions of molecules. Single molecule techniques can be used to image, manipulate or characterize the action of a single repair protein on a single strand of DNA. This allows search mechanisms to be probed, and the effects of force to be understood. These physical aspects can dominate a biochemical reaction, where at the ensemble level their nuances are obscured. In this paper we discuss so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 143 publications
(201 reference statements)
0
10
0
Order By: Relevance
“…Additionally, we are examining the role of UV-DDB in the recruitment of downstream NER or BER proteins at oxidative lesion sites to elucidate a role for UV-DDB in facilitating the repair process. The evidence of interplay between the two repair pathways could suggest direct interactions between BER and NER proteins, both on and off DNA, which needs further study by yeast-2-hybrid screens, co-IP and/or biochemical/biophysical methods, such as single-molecule in vitro techniques with a purified protein system or cell extracts to examine protein-protein and protein–DNA interactions at a defined lesion site ( 99 ). Moreover, these techniques can be used to examine, in real-time, how proteins act in unison to faithfully process DNA lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we are examining the role of UV-DDB in the recruitment of downstream NER or BER proteins at oxidative lesion sites to elucidate a role for UV-DDB in facilitating the repair process. The evidence of interplay between the two repair pathways could suggest direct interactions between BER and NER proteins, both on and off DNA, which needs further study by yeast-2-hybrid screens, co-IP and/or biochemical/biophysical methods, such as single-molecule in vitro techniques with a purified protein system or cell extracts to examine protein-protein and protein–DNA interactions at a defined lesion site ( 99 ). Moreover, these techniques can be used to examine, in real-time, how proteins act in unison to faithfully process DNA lesions.…”
Section: Discussionmentioning
confidence: 99%
“…UvrB also interacts with UvrC through a c-terminal coiled-coiled domain (DellaVecchia et al, 2007). We, working with Kad and coworkers, found that UvrB binds DNA tightropes in the presence of UvrC, but only if the two proteins are mixed together prior to adding to the DNA (Hughes et al, 2014). About 50% of these UvrBC complexes were motile on the DNA, displaying both random diffusion and anomalous 1D diffusion.…”
Section: Watching Uvra Uvrb and Uvrc Detect Damage In Real Timementioning
confidence: 95%
“…DNA in real-time at single-molecule scale (Kabata et al, 1993;Erie et al, 1994;Hughes et al, 2014). In order to visualize single protein molecules, the fundamental challenge is to achieve conditions where the fluorescence of one molecule can be differentiated from the background signal.…”
Section: Snapshots Of Ner and Ber Proteins Detecting Dna Damagementioning
confidence: 99%
“…The two most widely used methods to characterize the ability of a protein to processively scan DNA are singlemolecule fluorescence and ensemble biochemical processivity assays. In this review, we will highlight processivity-based assays and refer readers to excellent reviews on single-molecule fluorescence imaging techniques (911). However, it is worth discussing the advantages and limitations of both single-molecule and bulk biochemical assays and how the two techniques can complement each other.…”
Section: Methodsmentioning
confidence: 99%
“…Searching proteins can be directly observed scanning DNA molecules by using single-molecule fluorescence microscopy setups. Typically, proteins are visualized by attachment of quantum dots or small molecule fluorophores, through a variety of strategies (1115). The DNA is visualized by an intercalating fluorescent molecule called YOYO-1 or in some cases not at all.…”
Section: Methodsmentioning
confidence: 99%